The law and economics of international trade agreements - Sykes, A. O. (Northampton : Edward Elgar Publishing, 2023)
"From the pen of highly esteemed trade scholar Alan Sykes, this book presents a rigorous introduction to the law and economics of modern international trade agreements. With a bottom-up approach that requires neither a background in international trade law nor significant economics training, Sykes sets out to map and explain the complex dynamics of international trade agreements and institutions, synthesising legal analysis and cutting-edge economic research in order to present the reader with a sophisticated, holistic view of the field. Against the backdrop of the current impasse in both negotiation and dispute settlement at the World Trade Organisation, the book charts a clear path from the historical origins of trade law and the international system, to the current state of play, including unpacking the major areas of controversy. It exposits the economic theory of trade agreements, discusses the role of international trade law in domestic legal systems and analyzes the role of self-enforcement and formal dispute resolution mechanisms. It provides lucid and detailed analysis of the restrictions, exceptions, obligations and special measures that constitute the core building blocks of international trade rules, including the distinct features of international trade in services. With an international outlook, the book also addresses the role of China in the world trading system, looking at such issues as the credibility of market access commitments, China's industrial policies, "forced technology transfer" and currency manipulation. Providing an eloquent, thorough and technically astute overview of international trade agreements, this title will be invaluable to scholars and teachers of international trade across the disciplines of law, economics and political science"--
BIBINDX
Keywords: Commercial treaties; Foreign trade regulation